2019
DOI: 10.18203/2394-6040.ijcmph20190621
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attittude and practice among mothers of under five children on immunization

Abstract: Background: Many parents have poor understanding of vaccine preventable diseases (VPD) and many believe in false propagations about the contents, side effects and effectiveness of vaccines. Lack of good knowledge and positive attitude about childhood immunization was believed to be the root cause for resurgence of VPDs. Aim of the study was to assess the knowledge, attitude and practice regarding childhood immunization among mothers of under five children.Methods: A cross sectional study was done among mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Therefore, the results of the current study align with previous studies that were recently conducted in Saudi Arabia and with internationally trusted reports. The same aspects of a high level of knowledge, attitude, and practice were presented in other worldwide studies [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, the results of the current study align with previous studies that were recently conducted in Saudi Arabia and with internationally trusted reports. The same aspects of a high level of knowledge, attitude, and practice were presented in other worldwide studies [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 65%
“…Protection from diseases is one of the uttermost benefits that any country can offer to its people [ 1 ]. It is certain that vaccines are an essential part of a health system [ 2 ], an effective tool for controlling diseases in many countries around the world [ 3 ], and the most cost-effective mechanism for morbidity and mortality prevention that permits people to better protect themselves from particular bacteria and viruses [ 4 , 5 , 6 , 7 , 8 ]. In order to have the greatest protection against diseases, children should receive all their vaccinations within recommended intervals and at the appropriate age [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the 350 mothers interviewed, there was multiple sources of information but majority got information regarding immunization from health personnel (94.8%) followed by previous experience (3.1%), media and literature (1.2%) followed by family or friends (0.9%).Study done by K.K. Lamiya et al 22 in Kerala, India in 2017 showed health workers (77.4) as source of knowledge. Study by Boffaraj et al 16 in Libya in 2008 showed the most common source of information about the immunization of under five children was para medical workers (90%).…”
Section: Discussionmentioning
confidence: 99%
“…Study done by K.K. Lamiya et al 22 in Kerala, India in 2017 showed (87.7%), Nath B et al 20 in Lucknow, India in 2008 showed (44.1%), Boffaraj et al 16 in Libya in 2008 showed (81.1%), Adefolalu et al 14 in Nigeria in 2019 showed (86.4%), Nafila A.K 27 in 2019 revealed (93%), Joseph J 21 , Bengaluru in 2015 showed (86%), Rabannie Tariq Wani et al 24 in Kashmir, India in 2017 revealed (90%) were fully immunized.…”
Section: Discussionmentioning
confidence: 99%